Evaluation of holm oak (Quercus ilex) wood as alternative source for cellulose pulp - Eugenio, M E; Alaejos, J; Diaz, M J; Lopez, F; Vidal, T (CELLULOSE CHEMISTRY AND TECHNOLOGY, 2006)
Preservation of forests and increasing environmental awareness have focused research on the exploration of alternative resources for papermaking, a possible source being holm oak wood. The paper reports on the influence of some independent variables in the soda pulping of holm, oak wood \{[\}viz., temperature (135-195 degrees C), operation time (30-90 min) and active alkali concentration (10-20\%)] on the yield, hollocelulose, alpha-cellulose and lignin content, brightness, viscosity and kappa index of the pulps considered. By using a central, composite, factorial design, equations relating each dependent variable to different independent variables were derived, reproducing the experimental results for the dependent variables with errors below 10%. High pulp yield values were obtained under low operating variable conditions. To obtain the best results in brightness, viscosity and kappa index, operation under high values of the independent variables, the kappa index excepted, is necessary. To obtain a suitable value for this parameter, operation at low temperature is recommended. By applying TCF bleaching (A(1)OA(2)ZRP) in pulps obtained under extreme and central conditions of the pulping process, better values for kappa index (3.4) and brightness (83.8 ISO) result for the pulp obtained under maximum operating conditions. Nevertheless, considerable viscosity losses occur under Such conditions.
Keywords: Forestry residues; pulp; Quercus; soda pulp; Wood

Soda-anthraquinone, kraft and organosolv pulping of holm oak trimmings. - Alaejos, J; Lopez, F; Eugenio, M E; TAPIAS, R (Bioresource technology, 2006)
The operating conditions for an organosolv (ethyleneglycol) and two alkaline (soda-anthraquinone and kraft) processes for obtaining cellulose pulp and paper from holm oak (Quercus ilex) wood trimmings were optimized. A range of variation for each process variable (viz. temperature, cooking time and soda or ethyleneglycol concentration) was established and a central composite experimental design involving three independent variables at three different variation levels was applied. The results obtained with the three cooking processes used were compared and those provided by the kraft process were found to be the best. Thus, the tensile index values it provided (5.9-16.3 N m/g) were 23.7% and 41.5% better than those obtained with the soda-AQ and ethyleneglycol processes, respectively. Also, the kraft process provided the best burst index, brightness and kappa number values. Based on the optimum working ranges, the temperature and cooking time were the variables resulting in the most and least marked changes, respectively, in pulp properties.
Keywords: Ethyleneglycol; Forestry residues; Holm oak trimmings; Paper; Quercus